Are oxygen isotope fractionation factors between calcite and water derived from speleothems systematically biased due to prior calcite precipitation (PCP)?. (15th July 2021) - Deininger, Michael; Hansen, Maximilian; Fohlmeister, Jens; Schröder-Ritzrau, Andrea; Burstyn, Yuval; Scholz, Denis
Abstract: The equilibrium oxygen isotope fractionation factor between calcite and water ( 18 αcalcite/H2O ) is an important quantity in stable isotope geochemistry and allows in principle to infer temperature variations from carbonate δ 18 O if carbonate formation occurred in thermodynamic equilibrium. For this reason, many studies intended to determine the value of the oxygen isotope fractionation factor between calcite and water ( 18 αcalcite/H2O ) for a wide range of temperatures using modern cave calcite and the corresponding cave drip water or ancient speleothem carbonate and fluid inclusion samples. However, the picture that emerges from all of these studies indicates that speleothem calcite is not formed in thermodynamic equilibrium but under kinetic conditions, provoking a large variability of determined 18 αcalcite/H 2 O values. Here we present a conceptual framework that can explain the variability of 18 αcalcite/H 2 O values obtained by cave studies. Prior calcite precipitation (PCP) is calcite precipitation before cave drip water is dripping from the cave ceiling and impinges on the surface of a stalagmite or watch glass. Prior to the karst water dripping from the cave ceiling, PCP can occur in the karst above the cave as well as on the cave ceiling, the cave walls and on the surface of stalactites. We argue that PCP leads to increasing the δ 18 O value of the dissolved HCO3 − (δ 18 OHCO3- ), resulting in an oxygen isotope disequilibrium of the δ 18 OHCO3- values with respect to the δ 18 O value of water (δ 18 OH2O ). The oxygen isotope disequilibrium between HCO3 − and H2 O is re-equilibrated by oxygen isotope exchange between H2 O and HCO3 . Depending on the temperature, the re-equilibration time varies from hours to days and is usually much longer than the residence time of the drip water on stalactites, but much shorter than the time required to percolate through the karst. Therefore, while the oxygen isotope equilibrium between HCO3 − and H2 O is very likely re-established when PCP occurred in the karst, oxygen isotope disequilibrium conditions between HCO3 − and H2 O still prevail when PCP occurred inside a cave, e.g., on stalactites. If the oxygen isotope disequilibrium conditions between HCO3 − and H2 O is not re-established, the precipitated calcite will inherit the elevated δ 18 O value of the HCO3 − and not be in oxygen isotope equilibrium with the corresponding drip water. Consequently, if the 18 αcalcite/H 2 O value is calculated from cave calcite samples affected by PCP, the derived value will be systematically biased.